(untitled) (IAHS Medical Journal, 2024)
Background: Intraocular Lenses (IOLS) are permanent artificial lenses that can replace the eye’s natural lens to restore both near and distant vision. The aim of the study is to compare the accuracy of a single high quality. A scan measurement with that of the average three acceptable measurements in the calculation of IOL power. Materials and methods: Studied 180 eyes of 180 patients who underwent IOL surgery. All these patients underwent preoperative ocular biometry. Phacosurgery with posterior chamber intra ocular lens (PC IOL) implantation and clinical refraction was done in all patients between 4 to 12 weeks post operatively. The duration of the study was from January 2018 to December 2020 at Chittagong Parkview Hospital Ltd, Chattogram. Results: There was no significant difference between the two study group in measured axial length calculated emmertopic IOL power and the prediction of post operative refraction. Conclusion: The use of single high quality axial length measurement was as accurate as the mean of the three acceptable axial length measurement in the calculation of IOL power. IAHS Medical Journal Vol 6(1), June 2023; 30-33